2020
DOI: 10.3390/pr8040462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gd and Dy Concentrations in Layered Double Hydroxides on Contrast in Magnetic Resonance Imaging

Abstract: In this work, we explore the synthesis of layered double hydroxide (LDH) particles containing different molar ratios of Gd3+ and Dy3+ cations. A single crystalline phase was obtained for Zn2.0Al0.75Gd0.125Dy0.125-LDH and Zn2.0Al0.5Gd0.25Dy0.25-LDH, and their efficiency as contrast agents was evaluated by T1- and T2-weighted magnetic resonance imaging (MRI). Both GdDy-LDHs exhibited longitudinal relaxivity (r1) higher than a commercial reference. The highest contrast in the T1 mode was achieved with the Zn2.0Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The first route is easily achievable due to ability to exchange layer forming cations with other ones of a similar radius, while the latter is feasible due to elevated LDH ionexchange capacity. Applications of LDH substances and their derivatives include bioimaging [121,147,185], cosmetic [186] and therapeutic applications [77,173], development of novel drug and gene delivery platforms [155,187], tissue engineering [188][189][190], material science [1,4,191] and various sensing schemes based on LDH nanoparticles [192][193][194]. Below, we will focus on those involving LDH-biopolymer hybrids during materials preparation or functionalization.…”
Section: Biomedical Applications Of Ldh-biopolymer Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first route is easily achievable due to ability to exchange layer forming cations with other ones of a similar radius, while the latter is feasible due to elevated LDH ionexchange capacity. Applications of LDH substances and their derivatives include bioimaging [121,147,185], cosmetic [186] and therapeutic applications [77,173], development of novel drug and gene delivery platforms [155,187], tissue engineering [188][189][190], material science [1,4,191] and various sensing schemes based on LDH nanoparticles [192][193][194]. Below, we will focus on those involving LDH-biopolymer hybrids during materials preparation or functionalization.…”
Section: Biomedical Applications Of Ldh-biopolymer Hybridsmentioning
confidence: 99%
“…This may provide the diagnostic teams to better differentiate between diseased and healthy tissues to deliver more accurate results [120]. Another dual mode MRI contrast agent LDH was prepared by Andrade et al, who co-incorporated T 1 -type Gd(III) and T 2 -type Dy(III) within the LDH lamellae [121].…”
mentioning
confidence: 99%
“…Andrade et al prepared ZnAlGdDy-LDH with different Gd 3+ /Dy 3+ doping ratios (Zn 2.0 Al 0.75 Gd 0.125 Dy 0.125 -LDH and Zn 2.0 Al 0.5 Gd 0.25 Dy 0.25 -LDH) to evaluate their efficiency as contrast agents. 74 Relaxometry assessments showed that the best T 1 -weighted contrast was achieved with the former ( r 2 / r 1 ratio is 7.9), while the highest T 2 -weighted contrast was achieved with the latter ( r 2 / r 1 ratio is 22.5). Both of them displayed higher r 1 relaxivity than a commercial reference, indicating their potential to construct bimodal MRI contrast agents.…”
Section: Biomedical Applicationsmentioning
confidence: 91%
“…Andrade et al successfully prepared Gd/Dy-doped ZnAl-LDHs by this method. 74 Briefly, an aqueous solution containing hydrated nitrate salts of Zn, Al, Gd, and Dy was titrated with NH 4 OH under vigorous stirring. The final pH value of the solution was maintained at 10.0 and the resulting slurry was aged at room temperature for 24 h. The GdDy-doped ZnAl-LDHs were obtained after being washed with deionized water.…”
Section: Preparationmentioning
confidence: 99%
“…The paramagnetic effect of Gd in contrast enhancement of MRI images is by decreasing the relaxation times of T2 and T1 on protons. With the use of iron oxide, the dephasing rate of T2 * increases as well as T2 and T1 in the protons [7,8,9].…”
Section: Introductionmentioning
confidence: 99%